'PE should be an integral part of each school day': parents' and their children's attitudes towards primary physical education. Issue 4 (18th May 2020) - Coulter, Maura; McGrane, Bronagh; Woods, Catherine
ABSTRACT: Formation of positive attitudes is an objective in primary physical education. Children are more likely to engage in physical activity if they adopt positive attitudes towards physical education and parents play a large role in their development. This study explores parents' and children's attitudes toward their school's physical education provision. Overall, parents and children had positive attitudes towards their school's physical education programme. Children and parents valued fun and enjoyment in the physical education programme (affective component). Health and fitness as well as team sport discourses were felt important by parents, but they had little knowledge of the content of their child's physical education programme (cognitive component). There was little difference in either of the affective or cognitive components of attitude across gender or class groups in each of the areas explored except in responses about what physical education does and should do in their child's school. The school community must explore ways to inform parents about, and support their child's learning in, physical education ensuring positive attitudes (cognitive and affective) are fostered and encouraged towards influencing positive physically active behaviours.